The Results of a Three-Year Pneumococcal Vaccination of Children in Russia - Nikolay I. Briko; Vladimir A. Korshunov; Leyla S. Namazova-Baranova; Juriy V. Lobzin; Alexander A. Baranov; Natalia A. Kostenko; Marina V. Fedoseenko; Elena V. Kajtukova; Elena V. Vishneva; Natalia E. Tkachenko; Tatiana A. Kaljuzhnaya; Firuza Ch. Shakhtakhtinskaya; et al. (Педиатрическая фармакология)
Background. After inclusion of pneumococcal vaccination in the National Vaccination Schedule, it is very important to evaluate the efficacy of routine immunisation of the child population for more than 3 years. The obtained results provide opportunity to analyse the problems in achieving the goal, determine their causes, and suggest the ways of overcoming. Our aim was to study the results of a three-year period of pneumococcal vaccination of children. Methods. The quality of immunoprophylaxis of pneumococcal infection in the territory of the Russian Federation were assessed by analysing the coverage of vaccination and timeliness of its conduct after the inclusion of pneumococcal vaccine in the National Vaccination Schedule. The actual epidemiological efficacy of pneumococcal vaccination was assessed based on morbidity and mortality due to community-acquired pneumonia, incidence of acute otitis media among children. By questioning parents (n = 352) who applied to the Federal State Autonomous Institution of the Russian Federation Ministry of Health ‘National Medical Research Centre for Children’s Health, the timeliness of pneumococcal vaccination for infants was established. Results. In most regions, a high level of pneumococcal vaccination coverage was reached (87% of children). Despite the fact that the majority of children (73%) were vaccinated untimely. In particular, the results of a questionnaire survey conducted in the Moscow vaccination centre indicate insufficient awareness of parents for the need to vaccinate infants against pneumococcal infection by primary care professionals and, as a consequence, a low level of timely initiated vaccine introduction (40.1%). The introduction of routine prophylactic pneumococcal vaccination in Russia resulted in a 35% reduction in the death rate of children from community-acquired pneumonia, led to a decrease in the incidence of acute otitis media. Conclusion. The introduction of routine prophylactic vaccination of children against Streptococcus pneumoniae helps to reduce morbidity and mortality from pneumococcal infections. The surveillance system for community-acquired pneumonia requires further improvement. It is advisable to conduct an additional analysis on the reasons for refusals and medical exemptions to vaccination. It is important to increase the professional level of paediatricians in prophylactic vaccination.